Metabolic effects of parenteral nutrition enriched with n-3 polyunsaturated fatty acids in critically ill patients - Tappy, Luc; Berger, Mette Monica; Schwarz, Jean-Marc; Schneiter, Philippe; Kim, Seungki; Revelly, Jean-Pierre; Chiolero, Ren (CHURCHILL LIVINGSTONE, 2006)
Background & aims: n-3 fatty acids are expected to downregulate the inflammatory responses, and hence may decrease insulin resistance. On the other hand, n-3 fatty acid supplementation has been reported to increase glycemia in type 2 diabetes. We therefore assessed the effect of n-3 fatty acids delivered with parenteral nutrition on glucose metabolism in surgical intensive care patients. Methods: Twenty-four surgical intensive care patients were randomized to receive parenteral nutrition providing 1.25 times their fasting energy expenditure, with 0.25 g of either an n-3 fatty acid enriched-or a soy bean-lipid emulsion. Energy metabolism, glucose production, gluconeogenesis and hepatic de novo lipogenesis were evaluated after 4 days. Results: Total energy expenditure was significantly lower in patients receiving n-3 fatty acids (0.015+/-0.001 vs. 0.019+/-0.001 kcal/kg/min with soy bean lipids (P<0.05)). Glucose oxidation, lipid oxidation, glucose production, gluconeogenesis, hepatic de novo lipogenesis, plasma glucose, insulin and glucagon concentrations did not differ (all P>0.05) in the 2 groups. Conclusions: n-3 fatty acids were well tolerated in this group of severely ill patients. They decreased total energy expenditure without adverse metabolic effects. (C) 2006 Elsevier Ltd and European Society for Clinical Nutrition and Metabolism. All rights reserved.
Keywords: DE-NOVO LIPOGENESIS; DIETARY FISH-OIL; DEPENDENT DIABETES-MELLITUS; SYMPATHETIC-NERVE ACTIVITY; GLUCOSE-METABOLISM; PANCREATIC-CANCER; GENE-EXPRESSION; CARBOHYDRATE-METABOLISM; UNCOUPLING PROTEINS; INSULIN SENSITIVITY